The essentials of a just, sustainable and peaceful world - Eishan Jan, Mohammad Naqib (2018)
To the organizers of this timely event and to my good friend Mr. Phillgoo Jun, the coordinator International law Department, State Division, HWPL Thank you very much for inviting me as a keynote speaker to the 2nd Annual Commemoration of the Declaration of Peace and Cessation of War 2018. This is a very important event that has been held not only here in Malaysia but also in 173 branches of HWPL in other countries as well. Peace not war is the way forward – this is a very important proposition that HWTPL’s Declaration of Peace and Cessation of War (DPCW) advocates for. Let us join HWPL to say No to war and Yes to peace.